Resiliência física de um latossolo vermelho submetido ao pastejo bovino rotacionado - Koppe, Ezequiel (2018)
The expansion of dairy farming in the gaucho plateau, mainly under rotational grazing system, has generated soil physical changes by this system with loss of soil quality, which, in turn, is necessary to know the impacts of this system on the soil physical attributes, evaluating the duration of these changes and measure of soil resilience. The objective of this work was to evaluate the natural recovery of the soil physical attributes of a clayey Oxisol, managed under different intensities of cattle grazing and tramping as following: T1 = no grazing; T2 = consumption of 30% of the total amount of forage; T3 = consumption of 50% of the total amount of forage; T4 = consumption of 80% of the total amount of forage. The rotational grazing system used consisted of a grazing period of 4 hours, in average, then the animals were removed from the area and remained outside until the forage reaches an average height of 35 centimeters. This system was conducted for approximately seven months and after the animals were permanently removed from the area. The recovery of soil physical properties was monitored by soil sampling every three months during the period of one year. The physical properties evaluated were soil porosity, bulk density, soil air permeability, saturated hydraulic conductivity and infiltration rate. Soil samples were taken to determine the porosity and pore distribution using the computed tomography. After tomographic analysis, the samples were used to simulate the animal trampling by cyclic compressibility, in order to determine the cyclic compressibility index. After the loading cycles of 0, 1, 2, 4, 8, 16, 32, 64 and 120, was determined the air permeability. The grazing intensities negatively affected the physical quality of the soil. With the increase of grazing intensity there was reduction of total porosity, macroporosity, soil air permeability as well as bulk density increase. With the exclusion of grazing there is recovery of the structural quality of the soil, perceived by the increase of total porosity and macroporosity. The time of 90 days without grazing were enough to show the improvement of the values of total porosity and macroporosity. The relationship between soil air permeability and air-filled porosity is a good indicator of the physical quality of the soil, and this relationship reduces as the grazing intensity increases and was possible to verify the increase of this relationship with an increase in grazing exclusion time. Computed tomography is a great tool to characterize the structural quality of the soil, since it is possible to quantify the pore volume and it is possible to verify the shape, size, distribution and connectivity of the pores. The Euler number provided by the MAVI ToolIP could be used as an indicator of the structural quality of the soil. The soil elasticity index is affected by the compaction state, and as the initial compaction state increases, the elasticity index also increases. Rotated grazing, when handled properly, can be an important tool for sustainable production.